In Vitro Interactions of Antibiotic Combinations of Colistin, Tigecycline, and Doripenem Against Extensively Drug-Resistant and Multidrug-Resistant Acinetobacter baumannii - Park, Gyun Cheol (Ann Lab Med, 2016)
BACKGROUND: Acinetobacter baumannii infections are difficult to treat owing to the emergence of various antibiotic resistant isolates. Because treatment options are limited for multidrug-resistant (MDR) A. baumannii infection, the discovery of new therapies, including combination therapy, is required. We evaluated the synergistic activity of colistin, doripenem, and tigecycline combinations against extensively drug-resistant (XDR) A. baumannii and MDR A. baumannii. METHODS: Time-kill assays were performed for 41 XDR and 28 MDR clinical isolates of A. baumannii by using colistin, doripenem, and tigecycline combinations. Concentrations representative of clinically achievable levels (colistin 2 µg/mL, doripenem 8 µg/mL) and achievable tissue levels (tigecycline 2 µg/mL) for each antibiotic were used in this study. RESULTS: The colistin-doripenem combination displayed the highest rate of synergy (53.6%) and bactericidal activity (75.4%) in 69 clinical isolates of A. baumannii. Among them, thedoripenem-tigecycline combination showed the lowest rate of synergy (14.5%) and bacteri-cidal activity (24.6%). The doripenem-tigecycline combination showed a higher antagonistic interaction (5.8%) compared with the colistin-tigecycline (1.4%) combination. No antagonism was observed for the colistin-doripenem combination. CONCLUSIONS: The colistin-doripenem combination is supported in vitro by the high rate of synergy and bactericidal activity and lack of antagonistic reaction in XDR and MDR A. baumannii. It seems to be necessary to perform synergy tests to determine the appropri-ate combination therapy considering the antagonistic reaction found in several isolates against the doripenem-tigecycline and colistin-tigecycline combinations. These findings should be further examined in clinical studies.